2017
DOI: 10.1177/0961203317706557
|View full text |Cite
|
Sign up to set email alerts
|

Clinical associations of proinflammatory cytokines, oxidative biomarkers and vitamin D levels in systemic lupus erythematosus

Abstract: Background The abnormal biological activity of cytokines plays an important role in the pathophysiology of both systemic lupus erythematosus (SLE) and antiphospholipid syndrome (APS). Several studies have highlighted the association of vitamin D and certain pro-inflammatory cytokines with disease activity in SLE. However, there are limited data on the association of vitamin D and antiphospholipid antibodies (aPL) with various proinflammatory biomarkers in these patients and their relative impact on clinical ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
1
11
4
Order By: Relevance
“… IL interleukin, G-CSF granulocyte colony-stimulating factor, IFN interferon, TNF tumor necrosis factor a Mean (SD), in pg/mL b Data correspond to those patients with positive values as compared to healthy controls (above the threshold) [ 34 , 35 ] …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“… IL interleukin, G-CSF granulocyte colony-stimulating factor, IFN interferon, TNF tumor necrosis factor a Mean (SD), in pg/mL b Data correspond to those patients with positive values as compared to healthy controls (above the threshold) [ 34 , 35 ] …”
Section: Resultsmentioning
confidence: 99%
“…b Data correspond to those patients with positive values as compared to healthy controls (above the threshold) [ 34 , 35 ]…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A significantly high prevalence of vitamin D deficiency has been observed in patients with SLE in Saudi Arabia ( 114 ), Bahrain ( 115 ), the USA ( 116 , 117 ), Canada ( 118 ), Jamaica ( 119 ), Brazil ( 120 ), France ( 121 ), Hungary ( 122 ), Denmark ( 123 ), and Spain ( 124 , 125 ). In clinical studies on patients with SLE, significant inverse correlations were observed between serum levels of vitamin D and SLE disease activity index (SLEDAI) score in Malaysian ( 126 ), Taiwanese ( 127 ), Thai ( 128 ), Indian ( 129 ), Egyptian ( 130 , 131 ), Saudi Arabian ( 132 ), Brazilian ( 133 , 134 ), Australian ( 135 ), American ( 136 ), Hungarian ( 122 ), and Chinese ( 137 ) populations with an exception of Serbian SLE subjects ( n = 46) ( 138 ).…”
Section: Micronutrientsmentioning
confidence: 99%